- #1

- 71

- 0

m - M = 5 (log d) - 5

ok now.

(m - M) + 5 = 5(log d)

((m - M) + 5) / 5 = log d

d = 10 ^ ((m - M) +5) / 5)

is that right?

- Thread starter Aftermarth
- Start date

- #1

- 71

- 0

m - M = 5 (log d) - 5

ok now.

(m - M) + 5 = 5(log d)

((m - M) + 5) / 5 = log d

d = 10 ^ ((m - M) +5) / 5)

is that right?

- #2

Avodyne

Science Advisor

- 1,396

- 88

Yes, assuming the log is base 10.

- #3

- 71

- 0

- Last Post

- Replies
- 1

- Views
- 3K

- Last Post

- Replies
- 4

- Views
- 2K

- Last Post

- Replies
- 6

- Views
- 14K

- Last Post

- Replies
- 2

- Views
- 938

- Last Post

- Replies
- 3

- Views
- 989

- Replies
- 4

- Views
- 2K

- Last Post

- Replies
- 5

- Views
- 3K

- Replies
- 7

- Views
- 11K

- Replies
- 12

- Views
- 3K

- Last Post

- Replies
- 15

- Views
- 2K